2016
DOI: 10.1016/j.watres.2016.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Micropollutant degradation via extracted native enzymes from activated sludge

Abstract: A procedure was developed to assess the biodegradation of micropollutants in cell-free lysates produced from activated sludge of a municipal wastewater treatment plant (WWTP). This proof-of-principle provides the basis for further investigations of micropollutant biodegradation via native enzymes in a solution of reduced complexity, facilitating downstream protein analysis. Differently produced lysates, containing a variety of native enzymes, showed significant enzymatic activities of acid phosphatase, β-galac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 57 publications
1
49
0
5
Order By: Relevance
“…The enzyme-containing fractions from AS samples were obtained by sonication method. In brief, ice cooled samples of 10 mL sludge (~0.5 g TSS L -1 ) were individually homogenized using an ultrasonic cell disintegrator Sonics-VibraCell (BioBlock Scientific, France) with a power density of 1 W/mL for 5 (net) min in intervals of 5 s with 5 s breaks to avoid sample heating [37]. The crude cell lysate was subsequently purified through 0.45 μm and 0.20 μm syringe filters (Whatman 25 mm GD/X polyethersulfone membrane with glass microfiber prefilter).…”
Section: Reactive Oxygen Species (Ros) and Antioxidant Enzyme Activitymentioning
confidence: 99%
“…The enzyme-containing fractions from AS samples were obtained by sonication method. In brief, ice cooled samples of 10 mL sludge (~0.5 g TSS L -1 ) were individually homogenized using an ultrasonic cell disintegrator Sonics-VibraCell (BioBlock Scientific, France) with a power density of 1 W/mL for 5 (net) min in intervals of 5 s with 5 s breaks to avoid sample heating [37]. The crude cell lysate was subsequently purified through 0.45 μm and 0.20 μm syringe filters (Whatman 25 mm GD/X polyethersulfone membrane with glass microfiber prefilter).…”
Section: Reactive Oxygen Species (Ros) and Antioxidant Enzyme Activitymentioning
confidence: 99%
“…[16][17][18][19][20][21] The action of enzymes on OMPs is poorly investigated, and most studies have focused on oxygenases. [21][22][23] A recent study by Krah et al 24 tested the activity of a cocktail of extracted enzymes from activated sludge towards OMPs. By measuring several TPs and using several enzymatic inhibitors, they concluded that amide hydrolases could be involved in the biotransformation of acetaminophen, acetyl sulfamethoxazole, atenolol and bezafibrate, that oxidoreductases transform 10-OH-carbamazepine and that erythromycin is affected by hydrolases acting on ester bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our results suggest that extracellular hydrolases from typical wastewater microorganisms can hydrolyze polyesters under realistic WWTP conditions. The assumption is further supported by the fact that hydrolases such as esterases, lipases, and proteases are already being utilized successfully to enhance the bioremediation of effluents, and they are, furthermore, used for sludge pretreatment and flocculation reduction in wastewater . Enzymes could be applied in WWTPs both in free form and as immobilized enzymes, and both applications have their advantages and disadvantages.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23] Another approach to regulate and to enhancem icrobial hydrolytic activities in WWTPs is to add enzymef ormulations.I tw as shown in several studies that extracellular enzymes such as esterases, lipases, and proteasesc ould be utilized to enhancethe bioremediation of effluents and for sludge pretreatment and flocculation reductioni nw astewater. [24][25][26][27][28][29][30][31] Microbial lipases have been proven to be effective in reducing fat ando il contents in effluents dischargedb yt he dairy industry,s laughter houses, restaurants, hospitals, and health resorts. [25,32,33] Esterases have provent o play an important role in the biodegradation of many synthetic chemicals by hydrolyzing short-chain esters.…”
Section: Introductionmentioning
confidence: 99%